1989
DOI: 10.1007/bf01772820
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis in traumatic basal ganglia haematoma

Abstract: Twenty two patients with traumatic basal ganglia haematoma were studied. The mean Glasgow Coma Score on admission was 7. 17 patients had sustained high acceleration/deceleration injuries. The location and size of haematoma did not correlate with prognosis. Outcome was poor in 7 patients, while 8 patients died.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…The pioneering work of Adams et al [2] in 1986 identified TBGH as a distinct diagnosis rather than a spectrum of severe head injuries or diffuse axonal injuries, which was subsequently confirmed by many [1,5,6,7]. Its is mostly encountered in high-velocity trauma; however, falls from height are a frequent cause as well in children as recorded in 38% of our patients, which is similar to other studies [1,5,6,7,8,9]. …”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The pioneering work of Adams et al [2] in 1986 identified TBGH as a distinct diagnosis rather than a spectrum of severe head injuries or diffuse axonal injuries, which was subsequently confirmed by many [1,5,6,7]. Its is mostly encountered in high-velocity trauma; however, falls from height are a frequent cause as well in children as recorded in 38% of our patients, which is similar to other studies [1,5,6,7,8,9]. …”
Section: Discussionsupporting
confidence: 78%
“…Jaykumar et al [8] reported no difference in outcome with respect to location and size of the hematoma. Munemoto et al [4], in 1989, analyzed 5 cases of TBGH children and concluded that larger hematomas had a poorer prognosis than the spotty type hemorrhage in basal ganglia.…”
Section: Discussionmentioning
confidence: 99%
“…Intracerebral hematomas (ICH) (Figure 8) result from injury to intraparenchymal arteries or veins secondary to rotational strain or penetrating trauma 27, 83-85 and are usually located in the fronto-temporal white matter 48 or basal ganglia 83-85 . Differentiation from hemorrhagic contusions or TAI can be challenging 83-85 ; ICHs collect between relatively intact parenchyma in contrast to hemorrhagic contusions wherein hemorrhage is within a larger area of injured edematous brain 27 .…”
Section: Imaging Findings Of Traumatic Brain Injuriesmentioning
confidence: 99%
“…Differentiation from hemorrhagic contusions or TAI can be challenging 83-85 ; ICHs collect between relatively intact parenchyma in contrast to hemorrhagic contusions wherein hemorrhage is within a larger area of injured edematous brain 27 . Prognosis of isolated ICH is generally good 61 , but worsens when the lesion coexists with marked mass effect, TAI, or multiple basal ganglia hemorrhages 83, 84 . Temporal lobe hematomas are especially unpredictable, because even a relatively small lesion can lead to uncal herniation.…”
Section: Imaging Findings Of Traumatic Brain Injuriesmentioning
confidence: 99%
“…[2][3][4][5][6][7][8]13,16,[19][20][21] As we observed in the present case, many studies have shown a favorable outcome for patients with TBGH. …”
Section: Resultsmentioning
confidence: 76%